Tipologi intelektual Muslim dalam bidang kajian fikih: studi terhadap karya-karya fikih dosen STAIN Bengkulu - Sirajuddin M (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2012)
This study aims to examine the scientific trend of approach and theme of lecturer’s works of STAIN Bengkulu in the field of Islamic law (fiqh) and the scientific position of lecturer’s works of STAIN Bengkulu as Muslim intellectuals. This article is using two approaches, namely the conceptual approach and historical approaches, whereas measures of research was conducted by reviewing documentation as primer data and interviewing as sekunder data. The results showed that the scientific trend of approach and theme of lecturer’s works of STAIN Bengkulu was consists of three kinds: First, the normative trend of scientific approach and theme in Islamic law. This trend was categorized as “exclusive Muslim intellectualism”. Second, this trend began to expand the discourse of study on fikih, but it was not to integrate with Western scientific approach. This trend was categorized as “inclusive Muslim intellectualism”. Third, this study was more empirical and historical-sociological approach and theme in Islamic law (fikih) so that the discourse was more be able to answer the situation and condition of the people. This trend was categorized as “pluralist Muslim intellectualism”.